Making Sense of Localisation in China - Voices from A German multinational in Shanghai - Siegrist, Katharina Cornelia (2010)
In a globalising world economy the issue of localisation among foreign invested enterprises in China has been a hot topic throughout the last years. Not only in terms of sourcing and procurement, or more and more relocations of manufacturing or R&D to China localisation was discussed and supported by the Chinese government (e.g. subsidies for foreign firms investing in research laboratories in China), but also in terms of HR work and localisation of management positions. With huge numbers of Chinese college graduates coming on the job market every year (2009 it were 6.1 million (Huang, 2009)) and tightened laws on issuance of working permits for foreign employees in the PRC, subsidiaries of multinationals are forced to consider staffing policies, suitability and need for expatriate personnel sent to China more than before. This involves how to further implement HR strategies to build up local Chinese talent. With expatriates in many cases lacking market knowledge on China, the question is if well-educated, experienced, confident and able Chinese local talent meanwhile might not be equally or better suited for most managerial jobs than expatriates. The argumentation is that local market knowledge is inevitable for stable, effective and over all sustainable business success and performance in a country with such culture differences as exist between Asia and Europe or America. With a majority of studies and papers on HR localisation issues having been based on quantitative methods this study aims at three things that were identified as gaps in the literature. First, this research is conducted with qualitative methods and an ethnographic approach based on fieldwork during a time span of 11 weeks. In this time 67 complete semi-structured, in-depth interviews were gathered at three sites of a multinational enterprise in China. Second, this dissertation opposite to previous research on localisation mainly presenting HR managers’ and top managements’ view focuses on findings from observations and (in)formal interviews with employees. Displaying opinions and examples from 18 members of general staff, and nine line managers, supported with applied ethnography from observations and highlighted by a handful of top management voices and two experts this study sheds light on experience and difficulties with as well as ideas on localisation in a German invested company in the manufacturing industry in Shanghai in 2010. Lastly, in the literature frequently expatriate and top managements’ perception of local Chinese managers is a lack of experience while locals often do not understand this lack of trust in their abilities (Cheung, 2008). This dissertation aims at identifying reasons for this gap between the two perceptions that emerged from this case study. By helping researchers (and practitioners) to understand more background about this topic from the lens of those working along localisation strategies, employers in China might get an understanding for what staff perceive to be issues in their working environment concerning localisation. This could have a share in increasing management-employee communication and in doing so overall employee satisfaction and retention numbers.